(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize East Asian literature and current scientific evidence regarding Morinda officinalis (MO, Ba ji tian/Ba kich) as a supportive option in male infertility. Methods: This was a narrative review with a structured search. PubMed, CNKI, Wanfang, and accessible traditional medicine journals were searched through 12 November 2025 using English, Chinese, and Vietnamese keywords related to Morinda officinalis, male infertility, sperm, semen parameters, testosterone, and oligoasthenoteratozoospermia. The main evidence set included original in vitro, animal, and human studies directly assessing MO or its characterized constituents. Review articles were used only as background sources. Results: The evidence base remains dominated by experimental studies. Available data suggest that aqueous extracts, bajijiasu, and oligosaccharide-rich fractions may reduce oxidative stress, attenuate germ-cell apoptosis, improve testicular histology, enhance sperm count and motility, and modulate testosterone-related pathways. Clinical evidence specific to MO is sparse. No randomized, double-blind, placebo-controlled trial of standardized MO monotherapy in infertile men was identified. Human signals come mainly from multi-herb traditional medicine regimens in which MO is one component, making MO-specific effects difficult to isolate. Animal safety findings are generally favorable, whereas long-term human reproductive safety remains insufficiently documented. Conclusion: MO has biologically plausible and experimentally supported potential as an adjunct in integrative management of male infertility, but current clinical evidence is insufficient for routine use. Future trials should employ standardized preparations, WHO-based semen outcomes, and rigorous bias control.